2012
DOI: 10.5194/amt-5-1375-2012
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of turbulent dissipation rate retrievals from Doppler Cloud Radar

Abstract: Abstract. Turbulent dissipation rate retrievals from cloud radar Doppler velocity measurements are evaluated using independent, in situ observations in Arctic stratocumulus clouds. In situ validation data sets of dissipation rate are derived using sonic anemometer measurements from a tethered balloon and high frequency pressure variation observations from a research aircraft, both flown in proximity to stationary, ground-based radars. Modest biases are found among the data sets in particularly low-or high-turb… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

4
41
0

Year Published

2013
2013
2019
2019

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 41 publications
(47 citation statements)
references
References 40 publications
4
41
0
Order By: Relevance
“…Profiles of ε are estimated using temporal variance of the first Doppler moment, namely the mean Doppler velocity; details of the estimation method are given in Shupe et al (2012). The ε retrieval can be applied (contours, [dBZ]) observed from the vertically pointing MMCR radar at ASCOS over the week 25-30 August 2008.…”
Section: Measurements and Velocity Estimation Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Profiles of ε are estimated using temporal variance of the first Doppler moment, namely the mean Doppler velocity; details of the estimation method are given in Shupe et al (2012). The ε retrieval can be applied (contours, [dBZ]) observed from the vertically pointing MMCR radar at ASCOS over the week 25-30 August 2008.…”
Section: Measurements and Velocity Estimation Methodsmentioning
confidence: 99%
“…Relatively recent studies on AMPS in-cloud vertical velocity (w) have identified characteristic cloud overturning timescales on the order of 10 min (Pinto, 1998;Shupe et al, 2008aShupe et al, , 2012. These characteristic motions have been linked to the persistent nature of AMPS through the nearly continuous generation of cloud condensate, regulated in magnitude by ice crystal formation and precipitation processes (Shupe et al, 2008a).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Kouznetsov et al, 2007), Doppler cloud radars (e.g. Shupe et al, 2012) and combinations of these (e.g. Norton, 2006).…”
Section: Introductionmentioning
confidence: 99%
“…There are a lot of works on estimation of EDR based on radar remote sensing data. Many of radar methods and signal processing algorithms are based on estimating Doppler spectrum width (DSW) [1][2][3][4][5]. It is known that the DSW provides an overestimate of the turbulence EDR because not only turbulence contributes to the width of the spectrum.…”
Section: Introductionmentioning
confidence: 99%